Time distribution in different teaching-learning activities in BRAC schools - Shahjamal, Mirja M (Research and Evaluation Division, Brac, 2019)
This study aimed to explore different teaching-learning activities in BRAC schools, distribution of time in different activities and its relationship with students learning achievement. The study was done in 30 fifth grade NFPE schools located in a rural area. Fieldwork for the study was done in September 2001. Sixteen teaching-learning activities were found that occurred in the classrooms. It was observed that over two thirds of the total class time was spend in doing more than one activity. Evaluation of the students was the most time-consuming activity in the schools, which took 28% of the total time. The other popular activities were students' individual activities, correction of home task by the teachers, investigation of previous knowledge, teacher's discussion about text contents, blackboard use by the teacher and textbook reading by the students. Less amount of time was spent in roll call, textbook reading by the teacher and assembly. Not much variation was observed in this regard when data were analysed by subject or period. In general, the teachers spent more time in teaching Mathematics and less time for Bangia. No significant relationship was found between time distribution and performance ofthe students.